Positive Intraoperative Peritoneal Lavage Cytology is a Negative Prognostic Factor in Pancreatic Ductal Adenocarcinoma: A Retrospective Single-Center Study - Hirabayashi, Kenichi; Imoto, Akiko; Yamada, Misuzu; Hadano, Atsuko; Kato, Nobuaki; Miyajima, Youko; Ito, Hitoshi; Kawaguchi, Yoshiaki; Nakagohri, Toshio; Mine, Tetsuya; Nakamura, Naoya (Frontiers in Oncology, 2015)
Objective The aim of this study is to evaluate the prognostic significance of intraoperative peritoneal lavage cytology (PLC) in pancreatic invasive ductal adenocarcinoma. Methods Intraoperative PLC was evaluated in 162 patients with resectable pancreatic invasive ductal adenocarcinoma. The results were analyzed for correlations with clinicopathological parameters and/or prognoses. Results In the 162 cases of resectable pancreatic ductal adenocarcinoma, 18 (11%), 141 (87%), and 3 (2%) were positive, negative, and equivocal for intraoperative PLC, respectively. Intraoperative PLC positivity was associated with older patients (over 65 years), large tumor size (over 35 mm), tumor location in the body/tail of the pancreas, and distant metastasis. Univariate analysis showed that larger tumor sizes (≥35 mm, P = 0.001), lymph node metastases (P = 0.005), distant metastasis (P = 0.004), advanced stage (stage IIB or III, P = 0.006), advanced tumor histological grade (G3, P < 0.001), or positive intraoperative PLC (P = 0.002) are associated with a shorter survival. Multivariate analysis revealed that larger tumor sizes (≥35 mm, P = 0.026), lymph node metastasis (P = 0.021), advanced tumor histological grade (G3, P < 0.001), and positive intraoperative PLC (P = 0.002) were independent prognostic factors. Conclusion Intraoperative PLC is an independent prognostic factor for resectable pancreatic invasive ductal adenocarcinoma.